(untitled) (Journal of Foreign Language Studies, 2025)
This article presents the results of a pilot implementation of e-lessons in two practical language modules – A2-level Italian and Japanese for Tourism. The e-lessons were developed by lecturers from the relevant departments and uploaded to the University’s Learning Management System (LMS). Using descriptive and inferential statistical methods, this study analyzed experimental data from 197 foreign language students and survey responses from 149 students on various aspects of the two e-lessons per module. The study results indicate certain correlations between study time and test scores, as well as among various factors of the e-lessons, such as learning objectives, technology use, presentation format, and other criteria. This study holds both theoretical and practical significance in the context of Hanoi University’s efforts towards online education and digital transformation.